2021
DOI: 10.3390/pharmaceutics13010101
|View full text |Cite
|
Sign up to set email alerts
|

Peptides and Dendrimers: How to Combat Viral and Bacterial Infections

Abstract: The alarming growth of antimicrobial resistance and recent viral pandemic events have enhanced the need for novel approaches through innovative agents that are mainly able to attach to the external layers of bacteria and viruses, causing permanent damage. Antimicrobial molecules are potent broad-spectrum agents with a high potential as novel therapeutics. In this context, antimicrobial peptides, cell penetrating peptides, and antiviral peptides play a major role, and have been suggested as promising solutions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 173 publications
(177 reference statements)
0
18
0
Order By: Relevance
“…The antibacterial activity of dendrimer depends on the interaction of positive dendrimer charge and negative charge on the bacterial membrane surface, its ability to penetrate the bacterial membrane, and the destruction of the lipid bilayer. Cationic dendrimers have high antimicrobial activity due to their positive charge [85].…”
Section: Dendrimermentioning
confidence: 99%
See 2 more Smart Citations
“…The antibacterial activity of dendrimer depends on the interaction of positive dendrimer charge and negative charge on the bacterial membrane surface, its ability to penetrate the bacterial membrane, and the destruction of the lipid bilayer. Cationic dendrimers have high antimicrobial activity due to their positive charge [85].…”
Section: Dendrimermentioning
confidence: 99%
“…Dendrimer polyamidoamine (PAMAM) functionalized with sialic acid is very effective against murine influenza pneumonitis infection. Dendrimeric polyanionic can inhibit HIV, HSV, and other viruses by targeting the viral life cycle and preventing viral binding to host cells [85]. Anionic dendrimer PAMAM and cationic dendrimer have been shown to increase antiviral activity The Middle East respiratory syndrome coronavirus (MERS-CoV) [86].…”
Section: Dendrimermentioning
confidence: 99%
See 1 more Smart Citation
“…As linear peptides have low oral bioavailability because of their short half-life, alpha-helical AMP mutagenesis may be a useful approach for increasing antimicrobial activity [ 3 , 4 , 5 ]. Previous studies have reported that peptides [ 6 ] with linked n -alkyl acids, hybrid peptides [ 7 ] designed by combining α-helical fragments with core antimicrobial cationic fragments, copolymers based on AMPs [ 8 ], combinations [ 9 ] of AMP and antimicrobial agents [ 9 , 10 , 11 , 12 ], hybrid models of AMP and antimicrobial agents [ 13 ], hybrids comprised of AMPs with different mechanisms of action [ 14 ], dendrimers [ 15 ], and nanocarrier models [ 16 ] improve antimicrobial activity. However, in our previous study, AMP variants showed reduced antimicrobial activity against Candida albicans [ 17 ], which is the most common species causing fungal infections [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Falanga et al [10] focus on the impact of dendritic nanoplatforms based on antimicrobial, antiviral and cell penetrating peptides, as potent broad-spectrum agents. The review provides an interesting overview of the main concepts involved in the design of antimicrobial peptides for dendrimer decoration, aiming to promote the clinical translation of these promising conjugates.…”
mentioning
confidence: 99%